An Experimental Study of Air Flow and Heat Transfer Over In-Line Flat Tube Bank - Tahseen, Tahseen Ahmad; M. M., Rahman; M., Ishak (Universiti Malaysia Pahang, 2014)
An experimental study was made to investigate heat transfer and air flow around the flat tubes of in-line flat tube banks with laminar forced convection. Measurements were conducted for sixteen tubes in the flow direction; four rows of four tubes, three air velocities (0.6, 0.8 and 1.0 m/s) and Reynolds numbers ReDh = 527, 703 and 880, where Dh is the hydraulic diameter of the tube. The total heat flux supplied in all the tubes was 968, 2259 and 3630 W/m2, respectively. The study results indicate that the average Nusselt number of all the flat tubes increased by 23.7%-36.7% with Reynolds numbers varying from 527 to 880 with fixed heat flux; also the average Nusselt number increased by 11.78%-23.75% at varying heat fluxes of 968, 2259 and 3630 W/m2, respectively at Reynolds number Re = 703. In addition, the pressure drop decreased with the increase of Reynolds number. The Nusselt number-Reynolds number correlation was found to be and the correlation yielded good predictions of the measured data with the mean error R2 = 99.2%.